(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
After analysing the history of Western Dramafrom the point of view of self and self-fulfillment this chapter shall take upthe issues of self and self-fulfilment with regard to the plays in Sanskritliterature.